PENGARUH MEDIA SOSIAL TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Dian Laili Rahmawati; Sakdanur Nas; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study aims to determine the influence of using WhatsApp social media on the learning motivation of Economic Education students at the University of Riau. Data collection techniques by distributing questionnaires using a Likert scale.The population used in this study were students of Economic Education at the University of Riau, namely the 2017-2019 class with a total population of 231 people. The sample of this study was taken by probability random sampling using the Slovin formula and using a stratified random sampling technique, with a sample of 71 people. The data collected was then tabulated and analyzed using a simple linear regression analysis method. The results of this study indicate that the use of WhatsApp social media is high, namely 83.2%, the use of WhatsApp as a means of communication and information dissemination is very much needed by Economic Education students at the University of Riau, including communication and dissemination of learning information, while the learning motivation of Economic Education students is in the medium category64,9%.The use of WhatsApp social media has a positive and significant influence on the learning motivation of Economic Education students at the University of Riau with the regression equation Y=21,803+540X, it can be concluded that the influence of the use of WhatsApp social media (X) as a medium of communication and information dissemination on student learning motivation (Y) has an influence on positive with the results of R Square 0.288, the influence of using WhatsApp social media on learning motivation is 28.8%.Key Words: Social Media,Learning Motivation,Influence.